PT TAKEDA INDONESIA'S EDUCATIONAL CAMPAIGN STRATEGY #AYO3MPLUS VACCINE IN EFFORTS TO OVERCOME DENGUE HEMORRHAGIC FEVER - Gan Gan Giantika; Siti Qona’ah (Sean Institute, 2023)
Dengue fever disease dengue fever is a real threat to the people of Indonesia throughout the year. Ministry of Health data for 2019 shows that dengue fever is one of Indonesia's leading causes of child death. For this reason, special parties dealing with dengue hemorrhagic fever are needed. To support the government's program to reduce mortality due to dengue fever, PT Takeda Indonesia is carrying out an educational campaign in the form of the #Ayo3MplusVaksin movement on corporate web and social media platforms. In this study, researchers used a qualitative approach and case studies as a research method to describe PT Takeda Indonesia's Educational Campaign Strategy #Ayo3Mplus Vaccines to Overcome Dengue Hemorrhagic Fever in Indonesia. With a good response from the activities of the #Ayo3MplusVaksin movement, corporate Web and social media platforms can significantly impact the handling of dengue fever. Participants who participate provide experiences and also post on social media. This shows the positive effect of the #Ayo3Mplus Vaccine educational campaign activities to overcome dengue fever.